Pengaruh Variasi Kampuh Pada Pengelasan SMAW Terhadap Kekuatan Impact Sambungan Butt Join - Rohman, Rizatur Rohman (Jurnal Teknik Mesin, 2021)
ABSTRACTWelding is a process of joining two or more metal parts by using the heat energy. Aside from material selection as an affecting factor in welding process and quality, the type of Weld connection also important for obtaining mechanical properties in strength and toughness. The aim of the study was to decide the effect of welding joint type U, X and V to the microstructure and impact strength of the butt joint connection. This study uses ST 41 steel with 10x10x60 mm as the specimen dimensions for SMAW welding with E7018 electrodes. The results of this study concluded that the welding joint type U had 1.290 joules/mm2for the impact value average with 73.046% in pearlite percentage and 26.954% in ferrite percentage. The impact value of welding joint type X is 1.442 joules/mm2 in average with 64.108% in pearlite percentage and 35.892% in ferrite percentage. Meanwhile for the welding joint type V, the impact value average is 1,567 joules/mm2 with 73.046% as the pearlite percentage and 26.954% as the ferrite percentage. The microstruture changing during the welding process caused the differences between impact values in the welding results. The more and denser the pearlite element, the greater the impact strength and vice versa. Â Keywords: SMAW welding, impact value, microstructure, ST 41 steel, welding joint variations.